Preliminary study of a traditional Chinese medicine formula in systemic lupus erythematosus patients to taper steroid dose and prevent disease flare-up - Yen-Nung Liao; Ching-Shen Liu; Tong-Rong Tsai; Yu-Chiang Hung; Shun-Jen Chang; Hong-Long Lin; Ying-Chou Chen; Han-Ming Lai; Shan-Fu Yu; Chung-Jen Chen (Kaohsiung Journal of Medical Sciences, 2011)
Systemic lupus erythematosus (SLE) is a chronic systemic autoimmune disease. Prolonged complete remission is rare. Most patients with SLE need long-term treatment with glucocorticoid and immunomodulators. However, side effects because of the above medications are common. We evaluated the effect of adding-on Dan-Chi-Liu-Wei combination (DCLWC) on SLE patients with conventional therapy in tapering steroid and preventing disease flare-up. This was a double-blind and randomized controlled trial. Sixty-six SLE patients were recruited into this study and 53 patients who fulfilled the 1997 revised criteria for the classification of SLE with an SLE disease activity index (SLEDAI) score of 2–12 and a steroid (measured with prednisolone) daily dose of less than 20 mg/d were enrolled. The patients were randomized into either an experimental or control group. We checked the urine analysis, hemogram, liver function, renal function, C3, C4, erythrocyte sedimentation rate, and anti-dsDNA, evaluated the SLEDAI score, and recorded the steroid dose at 0 months, 3 months, and 6 months, respectively. After 6 months of study, the C4 and blood urea nitrogen level revealed a statistically significant difference in either group. There was a tendency toward a decreased SLEDAI score in the experimental group (p=0.083) but not in the control group (p=0.867). The steroid dose was not statistically significant in either group. Renal function and liver function revealed no statistically significant statistics changes in either group. Adding-on DCLWC to conventional therapy for the treatment of SLE was safe and might have a borderline effect in decreasing disease activity, but it was not possible to taper the dosage of steroid after 6 months of clinical trial. Therefore, a long-term follow-up and a large-scale study are necessary to confirm the effect of DCLWC.